Young adults' perception of parenting style: A retrospective exploration - Sukanya Rajan; Janardhana Navaneetham; Mariamma Philip; D Muralidhar (Wolters Kluwer Medknow Publications, 2020)
Introduction: This study sought to understand the perception of parenting style among young adults using qualitative method. Methods: Five focus group discussions were carried out with 29 participants. A self-prepared semi-structured interview, face validated by experts in the field and socio demographic sheet and focus group discussion guide was used for collecting the data. The data were transcribed and thematically analyzed. Results: The overarching themes were privacy, control, autonomy, discipline, love, and warmth and unconditional acceptance of parents. Conclusion: Sociocultural background and culture seems to be one of the strongest determinants in assessing the perception of parenting style among young adults.